STUDY OF ANTI-PEPTIDYL ARGININE DEIMINASE 4 AUTO ANTIBODIES IN RHEUMATOID ARTHRITIS PATIENTS AND THEIR CORRELATION WITH ANTI-CYCLIC CITRULLINATED PEPTIDE ANTIBODIES IN TELANGANA POPULATION - RAJKUMAR GUNDU; LAKSHMI PRABHA S; PONNUDHALI D (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: This study aimed to evaluate the role of anti-peptidyl arginine deiminase 4 (PADI4) autoantibodies in the early diagnosis of rheumatoid arthritis (RA) and their association with Disease Activity Score 28 (DAS28) and anti-cyclic citrullinated peptide (anti-CCP) antibodies. Methods: A case–control study involving 196 subjects, 98 patients of confirmed RA patients and 98 healthy controls matched in age and sex, was carried out at Rheumatology department of Chalmeda Anand Rao Institute of Medical Sciences (CAIMS), hospital. Detailed history is taken. Patients were included after following the inclusion and exclusion criteria, getting informed consent from patients, and approved by the institutional ethical committee of CAIMS. Appropriate statistical analysis will be done after collecting data. Statistical Package for the Social Sciences version 25 was used for further statistical analysis. p<0.05 was considered as statistically significant, DAS28, rheumatoid factor (RF), Erythrocyte sedimentation rate, anti- CCP, antibodies, and anti-PADI4 antibodies were measured in RA patients and controls BY ELIAS sandwich method. Results: Anti-PADI4 and anti-CCP antibody levels were significantly elevated in RA patients (p<0.001). Anti-PADI4 showed 68% sensitivity and 98% specificity, whereas anti-CCP had 84% sensitivity and 98% specificity. Combined testing increased diagnostic sensitivity to 90%. Anti-PADI4 levels showed positive correlations with DAS28 (r=0.54, p=0.006), anti-CCP (r=0.79, p<0.00001), and RF (r=0.62, p=0.0001). RA patients positive for anti- PADI4 had significantly higher DAS28 scores, RF, and anti-CCP levels than those negative for anti-PADI4. Anti-PADI4 also identified some anti-CCP-negative RA cases. Conclusion: Serum anti-PADI4 Auto antibodies give an important diagnostic value with correlation with anti-CCP antibodies and DAS28